PEMAHAMAN AKUNTANSI DAN AKUNTABILITAS MAHASISWA PENERIMA BEASISWA (Studi pada Mahasiswa Fakultas Ekonomika dan Bisnis UKSW) - David Adechandra A. Pesudo; Maylinda Adriani Putri; Supatmi Supatmi (Dinamika Akuntansi Keuangan dan Perbankan, 2016)
The purpose of this study is to describe the level of accounting comprehension and the accountability of educational fee and to describe the relationship between the level of accounting comprehension and the accountability of educational fee. This is a descriptive study by using the primary data which were collected by distributing the questionnaires and doing the interview with the respondents, the students of Economics and Business Faculty of Satya Wacana Christian University who are obtaining the scholarship. The results from 82 respondents showed that their average level of accounting comprehension was on the less comprehend range (64,02) with the accountability of educational fee was on the accountable range (82,40). Based on the correlation test, there was no correlation between the level of accounting comprehension and the accountability of educational fee. The result of this study also confirmed that the accountable behavior of the students of Economics and Business Faculty of Satya Wacana Christian University who are obtaining the scholarship was included in the second intention factor of the planned behavior theory which is called the normative beliefs. In this case, they behaved to be accountable because of the third party’s encouragement and based on their own agreement.  Keywords: the level of accounting knowledge, the accountability of educational fee, theory of planned behavior, students